2000
DOI: 10.1016/s1053-5357(00)00062-7
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude and gratuity: a meta-analysis of research on the service-tipping relationship

Abstract: The relationship between tip size and evaluations of the service was assessed in a meta-analysis of 7 published and 6 unpublished studies involving 2,547 dining parties at 20 different restaurants. Consistent with theories about equity motivation and the economic functions of tipping, there was a positive and statistically significant relationship between tip size and service evaluations. However, that relationship was much smaller than is generally supposed. The confounding effects of customer mood and patron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
210
2
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 208 publications
(237 citation statements)
references
References 19 publications
23
210
2
2
Order By: Relevance
“…Previous empirical studies have confirmed this prediction (see in particular Bodvarsson and Gibson (1997) and Lynn and McCall (2000)). However, we now test for other features of an efficient tipping contract.…”
Section: Tips Depend On Service Qualitysupporting
confidence: 61%
See 1 more Smart Citation
“…Previous empirical studies have confirmed this prediction (see in particular Bodvarsson and Gibson (1997) and Lynn and McCall (2000)). However, we now test for other features of an efficient tipping contract.…”
Section: Tips Depend On Service Qualitysupporting
confidence: 61%
“…2 Previous empirical studies have also found that tip increases with service quality (see in particular Bodvarsson and Gibson (1997), and Lynn and McCall (2000)). a simple theoretical model for the determinants of tipping behavior and then investigate whether our observed tipping behavior is consistent with this model.…”
Section: Introductionmentioning
confidence: 96%
“…However, As important as the service quality/tipping relationship is, many researchers have different opinions about the relationship. Lynn and McCall (2000) showed that parties that rate service quality highly leave larger tips than those parties who rate service less highly. However, the effect was relatively small as it can account for less than 2 percent to almost 5 percent of the tipping variability.…”
Section: Service Qualitymentioning
confidence: 99%
“…The question here is do tipping habits differ between first time customers and repeat customers. Lynn and McCall (2000) showed that frequent patrons tend to base their tip amount on a percentage of the bill size more often than do infrequent patrons. Furthermore, frequent patrons tend to tip a higher percentage compared to infrequent patrons.…”
Section: Patronage Frequencymentioning
confidence: 99%
See 1 more Smart Citation